Interdisciplinary Relationship Of Linguistic And Educational Perspectives In The Arabic Text Of The Hadith Of Gabriel/ العلاقة البينية للمنظورين اللغوي والتربوي في النص العربي لحديث جبريل - Aboueldahab, Aboueldahab Elbadry Ali (Ijaz Arabi Journal of Arabic Learning, 2025)
This research aimed to reveal the interdisciplinary intersections of the linguistic and educational perspectives in the Hadith of Gabriel and how to utilize the linguistic and educational implications within this Hadith to develop the educational context through an in-depth interdisciplinary reading from both the linguistic and educational perspectives. This reflects the importance of the linguistic component in the prophetic explanation of this Hadith in enhancing the educational environment. A descriptive-analytical approach was used to review previous research and studies on Hadith analysis. The linguistic structure was analyzed from four aspects: lexical implications, rhetorical implications, pragmatic implications of its terms, and verbal and non-verbal communication mechanisms. The inductive approach was used to extract the educational reflections of these aspects, supported by clear evidence. In presenting the results, the PEEL qualitative analysis method (Point, Evidence, Explanation, Link) was used to analyze the results of the qualitative research. The research findings resulted in a set of linguistic mechanisms at the levels of lexicon, rhetoric, pragmatics, and communication used in the Hadith of Gabriel, which had various educational implications related to stimulating learning motivation, classroom management, formulating oral questions, diversifying stimuli, reinforcement, and lesson closure. The research also highlighted utilizing these mechanisms to develop the educational context.